Enhancing Java RMI with Asynchrony through Reflection - Akin, Orhan; Erdogan, Nadia (Springer Berlin Heidelberg, 2009)
Java RMI’s synchronous invocation model may cause scalability challenges when long duration invocations are targeted. One way of overcoming this difficulty is adopting an asynchronous mode of operation. An asynchronous invocation allows the client to continue with its computation after dispatching a call, thus eliminating the need to wait idle while its request is being processed by a remote server. This paper describes an execution framework which extends Java RMI functionality with asynchrony. It is implemented on top of RMI calls, using the thread pooling capability and the reflection mechanism of Java. It differs from previous work as it does not require any external tool, preprocessor, or compiler and it may be integrated with previously developed software as no modification of target remote objects is necessary.